Thermo-mechanical-metallurgical modelling, validation and characterization of 42CrMo4 steel processed by directed energy deposition. (September 2022) - Cooke, Shaun; Sweet, Greg; Ahmadi, Keivan; Bishop, Paul; Herring, Rodney
Abstract: In this study, a sequentially coupled thermo-mechanical-metallurgical (TMM) finite element (FE) model for the directed energy deposition (DED) process is developed in ABAQUS/CAE. Due to the large majority of previously published FE models centered around Ti-6Al-4V and Inconel® alloys, this study applies a similar modelling approach for 42CrMo4 steel - a medium carbon alloy chemically equivalent to AISI 4140 steel. In addition to predicting the temperature history, residual stress, substrate distortion and metallurgical phase fractions, this model also incorporates the solid-state transformation strains derived from the thermal history directly into the mechanical analysis. This contribution to strain is known to have a significant effect on the resulting residual stresses for alloys with allotropic phase transformations. Moreover, a pre-processing framework is implemented and validated to enable modelling of complex geometries and laser trajectories. Four experimental case studies were conducted to validate the predictions of the presented model. The case studies consist of three separate thinwall geometries fabricated with varying dwell times and a cube with a more complex laser trajectory. The predicted temperature history, residual stresses, and substrate distortion are compared with in-situ temperature measurements and post-build surface residual stress and distortion profile measurements. The microstructural constituents of each case are also examined by optical and electron microscopy and compared with the simulated phase fractions. While the model predictions generally agree with experimental observations, distortion predictions are more accurate in higher dwell-time prints while phase fraction predictions show the opposite trend. Furthermore, the overestimation of martensite in the case with the longest dwell time may have caused the over prediction of tensile residual stress on the surface.